Urgensi Bimbingan Konseling Karir dengan Pemantapan Cita-Cita pada Siswa SMP Dalam Menghadapi Era Society 5.0 - Ardies, Annisaq; Fauziyah, Nur (JURNAL KONSELING GUSJIGANG, 2023)
The era of Society 5.0 is an era where the world will be directed or brought into concepts that apply technology. This article aims to determine: (1) the ability of students to recognize their talents and to know their aspirations, and (2) the urgency of student career counseling in facing the era of Society 5.0. The subjects of this study were 17 students at a public junior high school in Batang Regency, Central Java. Based on the results of research and discussion, it can be concluded that students have feelings that are aware of themselves and who they are that are fragile so these students have an attitude that is more inclined to depend on others and cannot recognize themselves well. So there is an urgency to provide guidance and direction given by the teacher, especially in providing an overview of goals and careers that have a relevant relationship with the abilities, advantages, and talents possessed by students in facing the Society 5.0 era because in this era it is possible that in In the next few years, the role of humans in overcoming several problems in people's lives can be replaced by technology.